Employee Retention at PT Pos Indonesia: Job Satisfaction as a Mediator - Aseanty, Deasy; Madi, Muhammad Reza; Gunawan, Andreas Wahyu (Jurnal Manajemen, 2025)
This study aims to analyze the Influence of Employee Participation and Self-Efficacy on Employee Retention mediated by Job Satisfaction at PT—Pos Indonesia in Central Jakarta. The data collected were 150 respondents from 26 KCP PT. Pos Indonesia Central Jakarta using Purposive Sampling data collection techniques. The data collected in this study were primary data by distributing questionnaires online using Google Form. Validity and reliability testing, descriptive statistical data analysis by finding the average and hypothesis testing were carried out using SPSS Version 21 and Amos Version 21. The results of this study indicate that Employee Participation and Self-Efficacy mediated by Job Satisfaction have a significant positive effect on Employee Retention. This study is expected to provide an influence for PT. Pos Indonesia Central Jakarta to improve Employee Participation, Self-Efficacy, Job Satisfaction, and Employee Retention of all employees.